No evidence for precopulatory inbreeding avoidance in Drosophila melanogaster - Tan, C; Løvlie, H; Pizzari, T; Wigby, S (2012)
Inbreeding depression can lead to the evolution of inbreeding avoidance before or after mating. However, despite widespread evidence of inbreeding depression, studies of inbreeding avoidance have generated different results across populations or species. These differences could potentially reflect the confounding effects of factors such as magnitude of inbreeding depression, sex, social familiarity, state of primary sexual receptivity and mating history. We examined the influence of these proximate factors on precopulatory inbreeding avoidance in a laboratory-adapted, outbred population of Drosophila melanogaster. We found a significant but low coefficient of inbreeding depression based on egg-adult viability measures. Controlling for sex-specific responses, familiarity, sexual receptivity and mating history, we found no evidence of precopulatory inbreeding avoidance. Mate choice of virgins was random with respect to relatedness and measurements of courtship frequency, mating latency and mating duration did not indicate any preference for unrelated partners. In fact, the only evidence for differential sexual behaviour in response to relatedness was that males first mated to unrelated females were significantly faster to remate with related females than with unrelated females. These results suggest that inbreeding avoidance may be limited in outbred populations of D. melanogaster, and fit theoretical predictions that inbreeding is not selected against in either sex when the coefficient of inbreeding depression is relatively low. © 2012 The Association for the Study of Animal Behaviour.